Pathological diagnosis of pulmonary large cell neuroendocrine carcinoma by endobronchial ultrasound‐guided transbronchial needle aspiration. Issue 2 (22nd December 2017) - Inage, Terunaga; Nakajima, Takahiro; Fujiwara, Taiki; Sakairi, Yuichi; Wada, Hironobu; Suzuki, Hidemi; Iwata, Takekazu; Chiyo, Masako; Nakatani, Yukio; Yoshino, Ichiro
Abstract : Background: Pulmonary large cell neuroendocrine carcinoma (LCNEC) is a relatively rare subtype of lung malignancy. According to revised 2015 World Health Organization (WHO) criteria for the pathological diagnosis of LCNEC, neuroendocrine markers must be examined by immunohistochemistry. In this study, we reevaluated endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) samples of patients previously diagnosed with LCNEC using the revised WHO criteria. Methods: Clinical tissue samples that had been obtained by EBUS‐TBNA between January 2004 and December 2011, and that had been pathologically diagnosed as LCNEC according to the previous criteria, were reevaluated according to the revised WHO criteria. Results: The records of 471 lung cancer patients with mediastinal or hilar lymph node metastasis diagnosed by EBUS‐TBNA were analyzed. Thirteen patients were diagnosed with LCNEC; one of which was diagnosed based on cytology alone because the histological material was insufficient for a histological examination. Among the 12 cases in which a histological examination was performed, nine were diagnosed with possible LCNEC based on neuroendocrine marker positivity, while three were diagnosed with suspected LCNEC because they did not meet the immunostaining criteria. The patient who was cytologically diagnosed was found to have non‐small cell carcinoma with neuroendocrine morphology. Conclusion: LCNEC could be pathologically diagnosed based on 2015 WHO criteria using EBUS‐TBNA samples.